Achieving a "Grand Convergence" in Global Health by 2035: Rwanda Shows the Way; Comment on "Improving the World's Health Through the Post-2015 Development Agenda: Perspectives From Rwanda" - Gavin Yamey; Sara Fewer; Naomi Beyeler (Kerman University of Medical Sciences, 2015)
Global Health 2035, the report of The Lancet Commission on Investing in Health, laid out a bold, highly ambitious framework for making rapid progress in improving global public health outcomes. It showed that with the right health investments, the international community could achieve a "grand convergence" in global health-a reduction in avertable infectious, maternal, and child deaths down to universally low levels-within a generation. Rwanda's success in rapidly reducing such deaths over the last 20 years shows that convergence is feasible. Binagwaho and Scott have argued that 5 lessons from this success are the importance of equity, quality health services, evidence-informed policy, intersectoral collaboration, and effective collaboration between countries and multilateral agencies. This article re-examines these lessons through the lens of the Global Health 2035 report to analyze how the experience in Rwanda might be generalized for other countries to making progress towards achieving a grand convergence.